(untitled) (Tidsskrift for Praktisk Teologi, 2020)
The nature of the relationship between theological education and the church is widely disputed.Innovations in seminary training and the rapidly changing context in which ministry is carriedout have made it difficult to define their precise relationship. For a variety of reasons many in thechurch have come to distrust the integrity of theological education. And yet, on closer inspection,school and church have much in common, including their mission, a common worship life, and,most definitively, their handling of the gospel. In this, the seminary is preliminary to the life of acongregation. Its ordered existence is established for the sake of the congregation. The seminaryis charged with four major tasks. They are hermeneutical, contextual, performative, and forma-tive. The hermeneutical task introduces the student to the reading and interpretation of the Bible,theological classics, and other important literature. The contextual task assesses the immediateand wider «world» in which the church exercises its ministry. The performative task trains thestudent in pastoral and ecclesial leadership. It includes skills in preaching, teaching, liturgicalleadership, counseling, and administration. The formative task is the most difficult to define.Through the many activities that make up a student’s education, the formative task endeavors toinscribe pastoral character in the learner. In an era that has seen seminary training adjust its con-tent to sociological and media influences, this paper asks seminaries to form persons for ministryin community through prayed engagement with the gospel. «Teach us to pray» symbolically repre-sents the greatest of all seminary enterprises, one that, if grasped, will evoke the most creative andfaithful ministry in the church. «Teach us to pray» is counter-cultural in that it rejects trainingthat begins from demographics, politics, sociology, and psychology, and the many other disci-plines that have fashioned the so-called «professional» ministry. It may be that theological educa-tion, in itself, does not have the resources to produce a healthy ministry. This article suggests amethod for doing theological education that does not begin with the expertise of the academy andend with the passivity of the consumer church. The seminary should incorporate into its curricu-lum the wisdom of the most gifted practitioners of ministry. The answer is not more practicalcourses but an entire curriculum that is rooted in the lived and multiple realities of the church.